PENGARUH PERBEDAAN JENIS EMULGATOR PADA SEDIAAN LOTION EKSTRAK DAUN BIDARA (Ziziphus spina-christi L.) TERHADAP MUTU FISIK - Andi Nur Izzahtul Irwan; Zulfahmi Hamka (Jurnal Kesehatan Yamasi Makassar, 2026)
Abstract. Bidara leaves contain phenolics and flavonoids which are effective as antioxidants. To increase the use value of bidara leaves, they are made into lotion preparations. This research aims to see the effect of different emulsifiers on lotion preparations from bidara leaf extract (Ziziphus spina-christi L.). Bidara leaves were extracted using a maceration method using 96% ethanol solvent for 3x24 hours. This lotion preparation was made with varying concentrations of Anionic and Nonionic emulsifiers and then carried out a physical evaluation including organoleptic tests, homogeneity tests, pH tests of the preparations, adhesion tests and spreadability tests. The results of the physical evaluation of lotion preparations with different types of emulsifiers influenced the pH of the bidara leaf extract lotion preparations, and in the organoleptic test, they were green and brown in color, had a distinctive aroma of bidara leaf extract, and had a soft texture. The lotion preparation is mixed homogeneously, has spreadability and stickiness values ​​that meet the standard requirements.